Eğitimde kuram ve uygulama bağının kurulmasına yönelik felsefi bir araştırma - Vefa TAŞDELEN (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
It is aimed to deliberate the nature of relation between theory and practice in this article, and focused on importance the educational theory to educational practice, and the educational practice to educational theory. It is assumed that theory as a production style of the philosophy itself, and argued that has been found main theory essentialist, empirist and humanistic in the history of philosophy. The theoretic styles reflects on education as rationalist, idealist, pragmatist, existiantialist and hermeneutical educational theory. It is also aimed to form a stage system between philosophy and practice. Theory is somewhere which mediates philosophy and practice, it is the consciousness of practice. Also, educational theory mediates philosophy of education and educational practice. It guides educational practice. As it moves from the philosophy of education and educational practice, philosopy becomes more and more concrete. There is a mutual correlation between theory and practice. Theory improves practice and practice improves theory, as well. Regarding the above mentioned as its subject matter, this article takes attention to the significance of the theory of education in terms of educational practice, and the significance of educational practice in terms of edicational theory. And it emhasizes the fact that an effective educational action is based on the ideal synhesis of theory and practice. It also investigates whether there is a difference between educational theory and philosophy of education or not